1991
DOI: 10.1056/nejm199101033240103
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Follow-up after Placement of a Self-Expanding Coronary-Artery Stent

Abstract: Early occlusion remains an important limitation of this coronary-artery stent. Even when the early effects are beneficial, there are frequently late occlusions or restenosis. The place of this form of treatment for coronary artery disease remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
199
1
15

Year Published

1992
1992
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 683 publications
(219 citation statements)
references
References 14 publications
4
199
1
15
Order By: Relevance
“…For clinically defined stent thrombosis events, the associated 6-month mortality was 20.8%. These findings are consistent with the disastrous consequences of stent thrombosis reported in early studies 1,6,19,21,23,24 and are somewhat surprising because stent thrombosis events in our study patients were much more likely to occur while patients were still hospitalized. This is consistent, however, with a report by Hasdai et al 25 that showed poor clinical outcomes despite prompt restoration of blood flow after stent thrombosis.…”
Section: Cutlip Et Al Stent Thrombosissupporting
confidence: 82%
See 1 more Smart Citation
“…For clinically defined stent thrombosis events, the associated 6-month mortality was 20.8%. These findings are consistent with the disastrous consequences of stent thrombosis reported in early studies 1,6,19,21,23,24 and are somewhat surprising because stent thrombosis events in our study patients were much more likely to occur while patients were still hospitalized. This is consistent, however, with a report by Hasdai et al 25 that showed poor clinical outcomes despite prompt restoration of blood flow after stent thrombosis.…”
Section: Cutlip Et Al Stent Thrombosissupporting
confidence: 82%
“…[1][2][3][4] These studies also showed a reduction in the previously alarmingly high rates of stent thrombosis from 20% [5][6][7] to Ϸ3.5%, although this was achieved at the cost of aggressive anticoagulation with an associated high rate of bleeding complications. 1,2 More recently, studies using either routine high-pressure postdilation stenting or intravascular ultrasound guidance and antiplatelet therapy with aspirin and ticlopidine have reported reduced rates of stent thrombosis of 0.5% to 1.9% without an associated increased bleeding risk.…”
mentioning
confidence: 90%
“…ST occurred in up to 25% of the cases within the first 14 days in early experience. 3 ST is a very serious clinical event typically resulting in ST-elevation myocardial infarction (MI) in 70-80% of cases 4 with mortality rates that may be as high as 20-40%. 5 Aggressive initial attempts to tackle ST with high dose heparin, dextran and urokinase infusions lead to considerable morbidity and mortality with major bleeding occurring in up to 9% of the cases.…”
Section: Bare Metal Stents (Bms) -The Rise and Fallmentioning
confidence: 99%
“…The inability of the smooth muscle cells to regulate their own growth effectively results in neointimal hyperplasia, and vascular remodeling that may eventually hinder adequate blood flow due to luminal size reduction ultimately inducing major cardiac events (MACE) i.e. myocardial ischemia, infarction, thrombosis, or death (Serruys et al 1991;Serruys et al 1994;Sigwart et al 1987). The two major categories of restenosis for balloon angioplasty are angiographic restenosis, which is defined as a 50% reduction of luminal diameter at follow-up angiography, which is 25 to 50% of all cases, and clinical restenosis, which is defined as recurrent angina (chest discomfort), which occurs in 20 to 30% of patients (Hansrani, 2002).…”
Section: Pci and Coronary Restenosismentioning
confidence: 99%
“…Intracoronary stent implantation along with balloon angioplasty is highly effective in the treatment of acute vessel closure (Sigwart et al 1987;Roubin et al 1992;de Jaegere et al 1993a;Fischman et al 1994). However, bare metal stents are thrombogenic, and the benefit achieved at the expense of high-risk vascular complications (Schatz et al 1991;Serruys et al 1994;de Jaegere et al 1993b;Serruys et al 1991) must be considered. The use of stents has significantly improved the outcome of PCI.…”
Section: Hypothesismentioning
confidence: 99%